Peran manajemen laba dalam upaya meminimalisasi Tax Avoidance - Rida Ristiyana; Erwindiawan Erwindiawan; Nilta Rizkiyah; Sri Jaya Lesmana (Politeknik Ganesha Medan, 2025)
The purpose of this study is to examine the role of earnings management in efforts to minimize tax avoidance. The research sample met the criteria of 50 manufacturing companies listed on the Indonesia Stock Exchange during the 2014- 2022 period. The sampling technique used was the purposive sampling method with the number of observation data (n) = 274. The analysis tool used in the study is Panel Data Regression and to measure mediation is used path analysis through sobel tests. The results of the study in model 1 show that audit quality and capital intensity have a negative and significant effect on earnings management. On the other hand, the characteristics of the company have a positive and significant effect on earnings management. It is different with executive characteristics that do not affect earnings management. The results of the study in model 2 show that audit quality, executive characteristics, capital intensity, and company characteristics have no effect on tax avoidance. Meanwhile, earnings management has a negative and significant effect on tax avoidance. For the path analysis, the results were obtained that earnings management can mediate by strengthening the influence of audit quality on tax avoidance. On the other hand, earnings management cannot mediate the influence of executive characteristics, capital intensity and company characteristics on tax avoidance.